Mārtiņa Lapiņa fotografētais Aleksandra Zāmeļa portrets - Jamonte, Daiga (My University, 2022)
Godinot latviešu botāniķi un ģenētiķi Aleksandru Zāmeli 125 gadu jubilejā par mēneša priekšmetu Latvijas Universitātes Muzejs ir izvēlējies A. Zāmeļa portretu, ko fotografējis viens no 20. gadsimta pirmās puses izcilākajiem fotogrāfiem Mārtiņš Lapiņš. Raksts veltīts šai fotogrāfijai.

Honoring the Latvian botanist and geneticist Alexander Zāmel on his 125th anniversary, the Museum of the University of Latvia has chosen the portrait of A. Zāmel, photographed by one of the most outstanding photographers of the first half of the 20th century, Martins Lapins, as the object of the month. The article is dedicated to this photo.
Portrait of Alexander Zāmel photographed by Mārtiņš Lapins
Keywords: Research Subject Categories::NATURAL SCIENCES::Biology; Aleksandrs Zāmelis; Mārtiņš Lapiņš; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Cruciferae; fotogrāfijas vēsture; photography; portrets; portrait; botāniķis; botanist